Photoreceptor cells and eyes in Annelida - Purschke, Günter; Arendt, Detlev; Zur Hausen, Harald; Müller, Monika C. M. (Arthropod structure & development, 2006)
The evolution of photoreceptor cells and eyes in Metazoa is far from being resolved, although recent developmental and morphological studies provided strong evidence for a common origin of photoreceptor cells and existence of sister cell types in early metazoans. Photoreceptor cells are of two types, rhabdomeric and ciliary, depending on which part of the cells is involved in photoreception proper. A crucial point in understanding eye evolution is the explanation of the enormous structural diversity of photoreceptor cells and visual systems, given the general tendency for molecular conservation. One example of such diversity occurs in Annelida. In this taxon three types of photoreceptor cells exist: rhabdomeric, ciliary and phaosomous sensory cells. Whether the latter evolved independently or have been derived from one of the former cell types is still unresolved, since cilia and microvilli are found in these cells. These different photoreceptor cells are present in cerebral ocelli and eyes, in various ectopic ocelli and eyes situated in different places as well as in various photoreceptor-like sense organs. Whereas rhabdomeric cells mostly occur in connection with pigmented supportive cells, the other types are usually found with unpigmented supportive cells. Thus for the latter cells clear evidence for photoreception is still lacking in most cases. However, initial molecular-developmental investigations have shown that in fact ciliary photoreceptor cells exist within Annelida. Certain visual systems are only present during the larval phase and either replaced by the adult eyes or completely reduced during postlarval and adult stages. In the present paper the diversity of cerebral and extracerebral photoreceptor cells and ocelli as well as corresponding organs devoid of shading pigment is reviewed in Annelida.